Simultaneous Multi-Vessel Very Late Stent Thrombosis in Acute ST-Segment Elevation Myocardial Infarction - Yuefeng Chen; Michael Amponsah; Cyril Nathaniel (Case Reports in Cardiology)
Simultaneous multi-vessel very later stent thrombosis (VLST) is a very rare complication of percutaneous coronary intervention (PCI). We present a case of simultaneous multi-vessel VLST as the cause of acute ST-segment elevation myocardial infarction (STEMI). PCI of the culprit vessel was performed at acute presentation. Resolution of in-stent thrombosis in non-culprit vessels was noted on coronary angiography 2 days later. Our case suggests that PCI for culprit lesion in acute setting may be a reasonable option for simultaneous multi-vessel VLST.